A comparative study on the costs and returns of organic vs. inorganic farming practices at selected areas near Dhaka, Bangladesh - Islam, Md Arafat; Khan, Nazmul Ahsan; Bashar, Raisa (Research in Agriculture Livestock and Fisheries, 2019)
Inorganic farming is the norm in most areas of Bangladesh today, especially at croplands near Bangladesh’s capital - Dhaka. However, several recent studies have shown that such practices cause soil degradation overtime, consequently leading to long-term harm to the environment and economic profits. This long-term cost is often avoided by most farmers as inorganic farming is believed to fetch increased productivity/monetary gains, than its environmentally friendly, organic counterpart: the primary aim of this research was to find out the validity of this belief. The research used literature review and analysis of primary data collected about input costs, returns, crop yields, environmental effects, etc., from sixty respondents (mostly farmers and consumers involved in both types of farming), using one-on-one structured interviews, and three focus group discussions at the selected areas of Savar, Sreenagar and Rupganj, focusing primarily on two popular crops – tomato and corn; graphical and tabular analyses were conducted using MS Excel to propose interpretations and record findings. Keeping all other things constant and internalizing environmental externalities, while organic farming was found to produce around 50% and 33% less tomatoes and corns in net terms, respectively, than inorganic farming, the input costs and returns from one cycle of production were found to be lower (50%) and higher (around 200USD), respectively. Hence, from a long-run perspective, organic farming was concluded as the more cost-effective choice both in economic and environmental terms, given that the Dhaka market for organic products are managed better by the producers, consumers and government, alike. Res. Agric., Livest. Fish.6(2): 289-299, August 2019